Characterization of XR_311113.2 as a MicroRNA Sponge for Pre-ovulatory Ovarian Follicles of Goats via Long Noncoding RNA Profile and Bioinformatics Analysis - Tao, Hu; Yang, Juan; Zhang, Pengpeng; Zhang, Nian; Suo, Xiaojun; Li, Xiaofeng; Liu, Yang; Chen, Mingxin (Frontiers in Genetics, 2022)
Long noncoding RNAs (lncRNAs) were identified recently as a large class of noncoding RNAs (ncRNAs) with a length ≥ 200 base pairs (bp). The function and mechanism of lncRNAs have been reported in a growing number of species and tissues. In contrast, the regulatory mechanism of lncRNAs in the goat reproductive system has rarely been reported. In the present study, we sequenced and analyzed the lncRNAs using bioinformatics to identify their expression profiles. As a result, 895 lncRNAs were predicted in the pre-ovulatory ovarian follicles of goats. Eighty-eight lncRNAs were differentially expressed in the Macheng black goat when compared with Boer goat. In addition, the lncRNA XR_311113.2 acted as a sponge of chi-miR-424-5p, as assessed via a luciferase activity assay. Taken together, our findings demonstrate that lncRNAs have potential effects in the ovarian follicles of goats and may represent a promising new research field to understand follicular development.